أثر إستراتيجية النمو على موظفي إدارة الموارد البشرية ودورها في تحقيق الميزة التنافسية:دراسة تطبيقة على منظمة يونايتد الرياضية في دولة الإمارات العربية المتحدة - مبارك محمد علي الرملي الكتبي
The study aimed to identify the impact of the growth strategy on human resources management staff and its role in achieving competitive advantage, through a field study on United Sports Organization in the United Arab Emirates. The study tool was represented in the questionnaire that the researcher distributed to an purposive sampling of (400) individual employees of the organization in the emirates of "Abu Dhabi - Al Ain" in UAE. (390) questionnaires were retrieved, and (10) were missed. Several advanced statistical methods were used, including factor analysis using the SPSS program, confirmatory factor analysis. The study also used the Structural Equation Modeling using the AMOS program, in addition to an analytical descriptive approach. The researcher used the scientific theory of Taylor. The study reached many results, for the results of the independent variable (growth strategy) it was found that after the integration strategy the degree of relative strength reached 43.2%, while the percentage of neutrals was 1.5%. Moreover, the dimension of the diversification strategy the relative strength of the diversification strategy was 15.3%, while the percentage of neutrals was 0.97%, and for the dimension of the focus strategy the study relied on the criterion of relative strength as a criterion for measuring the focus strategy as a third factor in the strategy of the sports growth strategy and 25.7%. As for the results of the intermediate variable (human resources management), the relative strength of the afterpolarization was 36%, while the percentage of neutrals was 1.2%. The relative strength of the choice and appointment dimension was 32.2%, while the percentage of neutrals was 1.7%. Moreover, after training the relative strength of 29.7%, while the percentage of neutrals was 3.3%. While for the after-development of the employees, the relative strength of this dimension reached 32.4%, while the percentage of neutrals was 1.2%. Furthermore, the dimension of planning Career path has reached the degree of relative strength of 30.2%, while the percentage of neutrals was 2%, and in terms of the dimension of compensation and incentives, the relative strength was 23%, while the percentage of neutrals was 5%. With regard to the results of the dependent variable (competitive advantage), the relative strength of the cost reduction dimension was 27.5%, while the percentage of neutrals was 3.8%. And for the relative strength of the quality improvement was 32.1%, while the ratio of neutrals was 4.3%. The relative strength of the flexibility increase was 27.1%, the neutrals 1.5%. Finally, the relative strength of the innovation increase disfigurement was 37%, and the neutrals 3.9%.